1976
DOI: 10.1136/jcp.29.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid binding protein in acute myeloid leukaemia.

Abstract: SYNOPSIS Folic acid binding protein was estimated in the serum of 94 control subjects and a normal range was established. Raised levels were found in folate deficiency and chronic myeloid leukaemia. Considerably raised levels were found in untreated acute myeloid leukaemia, most often in cases with a marked monocytic element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that folate-binding protein maybe actively synthesised at a greater than normal rate by chronic granulocytic leukaemia cells (Da Costa and Rothenberg, 1974b). In AML leucocytes, the level of folate binding was invariably normal, even though Gorst et al (1976) found folate binding to be raised in the sera of patients with AML. The exact cause of this increased serum binding in AML remains to be determined.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that folate-binding protein maybe actively synthesised at a greater than normal rate by chronic granulocytic leukaemia cells (Da Costa and Rothenberg, 1974b). In AML leucocytes, the level of folate binding was invariably normal, even though Gorst et al (1976) found folate binding to be raised in the sera of patients with AML. The exact cause of this increased serum binding in AML remains to be determined.…”
Section: Discussionmentioning
confidence: 91%
“…Subsequently, a folate binding protein was found in granulocytes of women who were pregnant or taking oral contraceptives (Da Costa and Rothenberg, 1974a) and in the sera of normal subjects and patients with a variety of diseases (Rothenberg, 1973;Waxman and Schreiber, 1973;Zettner and Duly, 1974;Colman and Herbert, 1976;Gorst et al, 1976;Rothenberg and Da Costa, 1976).…”
mentioning
confidence: 99%
“…FABP was measured as in the previous study [3]. Heparinised blood was separated into its various cell types by the method of Summers et at.…”
Section: Methodsmentioning
confidence: 99%
“…In an earlier study [3], 6 normal females were found to have levels in excess of 300 pg/ml whilst the mean level of 94 controls was 76 pg/ml. Sera and leucocyte lysates from these people have been used to esti mate the molecular weight of FABP in normal people.…”
mentioning
confidence: 99%